Neotypification of Opuntia pilifera (Cactaceae; Opuntioideae) - Martínez-González, César Ramiro; Morales-Sandoval, José De Jesús (Phytotaxa, 2020)
Opuntia Miller (1754: no pagination) is a genus critical from both taxonomic and nomenclattural points of views (see e.g., Pinkava 2002, Griffith & Porter 2009, Majure et al. 2012). Many of the taxa belonging to this genus were described bases on materials collected by Old World naturalists (e.g., Arechavaleta 1905, Spegazzini 1905, 1925, Pontes et al. 2017). This led to publications of names based on plants grown under greenhouses conditions. Moreover, these names, although nomenclaturally valid, were often poorly described and usually no type was designated (see e.g., Haworth 1812, Pfeiffer 1837, Salm-Dyck 1850).